DNA methylation profiling reveals differences in the 3 human monocyte subsets and identifies uremia to induce DNA methylation changes during differentiation. Issue 4 (2nd April 2016) - Zawada, Adam M.; Schneider, Jenny S.; Michel, Anne I.; Rogacev, Kyrill S.; Hummel, Björn; Krezdorn, Nicolas; Müller, Soeren; Rotter, Björn; Winter, Peter; Obeid, Rima; Geisel, Jürgen; Fliser, Danilo; et al.
ABSTRACT: Human monocytes are a heterogeneous cell population consisting of 3 subsets: classical CD14++CD16-, intermediate CD14++CD16+ and nonclassical CD14+CD16++ monocytes. Via poorly characterized mechanisms, intermediate monocyte counts rise in chronic inflammatory diseases, among which chronic kidney disease is of particular epidemiologic importance. DNA methylation is a central epigenetic feature that controls hematopoiesis. By applying next-generation Methyl-Sequencing we now tested how far the 3 monocyte subsets differ in their DNA methylome and whether uremia induces DNA methylation changes in differentiating monocytes. We found that each monocyte subset displays a unique phenotype with regards to DNA methylation. Genes with differentially methylated promoter regions in intermediate monocytes were linked to distinct immunological processes, which is in line with results from recent gene expression analyses. In vitro, uremia induced dysregulation of DNA methylation in differentiating monocytes, which affected several transcription regulators important for monocyte differentiation (e.g., FLT3, HDAC1, MNT ) and led to enhanced generation of intermediate monocytes. As potential mediator, the uremic toxin and methylation inhibitor S-adenosylhomocysteine induced shifts in monocyte subsets in vitro, and associated with monocyte subset counts in vivo . Our data support the concept of monocyte trichotomy and the distinct role of intermediate monocytes in human immunity. The shift in monocyte subsets that occurs in chronic kidney disease, a proinflammatory condition of substantial epidemiological impact, may be induced by accumulation of uremic toxins that mediate epigenetic dysregulation.